Collaborative Governance Dalam Perbaikan Infrastruktur Jalan di Kota Pekanbaru Provinsi Riau - Dio Bella Yung; Afni Nooraini (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study investigates collaborative governance in road infrastructure repair in Pekanbaru City, Riau Province, driven by the urgent need to address the high number of damaged roads and the limitations of local government capabilities. Utilizing a qualitative method with a descriptive approach, data were gathered from interviews with five stakeholders, field observations, and supporting documents. The study applies collaborative governance theory by Emerson and Nabatchi to analyze road repair efforts in Pekanbaru, highlighting effective collaborative dynamics. Key findings reveal the establishment of a Coordination Team, role clarity, trust, and commitment among stakeholders as factors of success. Essential contributing elements include shared cooperation needs, consequential incentives, leadership support, and sufficient resources. However, challenges such as a volatile political climate, unequal information distribution, and power imbalances pose barriers to collaboration. Overall, the study concludes that collaborative governance in Pekanbaru's road infrastructure enhancement has yielded positive outcomes but calls for improvements in transparency, communication strategies, and the establishment of an integrated information system for effective progress monitoring. Additionally, independent oversight mechanisms are recommended to sustain equitable role distribution and responsibilities among all parties involved.